The nebula secret - Trueit, Trudi Strain (Trueit, Trudi Strain. Explorer Academy ;, 2018)
Twelve-year-old Cruz Coronado leaves his home in Hawaii to study and travel with other young people invited to attend the elite Explorer Academy in Washington, D.C., but a family connection to the organization could jeopardize his future.